2019
DOI: 10.1002/14651858.cd009219.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Medical interventions for the prevention of platinum-induced hearing loss in children with cancer

Abstract: Medical interventions for the prevention of platinum-induced hearing loss in children with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 58 publications
0
20
0
2
Order By: Relevance
“…5,10,48,57 A systematic review by van As et al described two randomized controlled trials (RCTs) and one controlled clinical trial evaluating amifostine as a possible otoprotective intervention in childhood cancer patients. 50 Due to methodological limitations of these clinical trials, there currently is no evidence that otoprotection with amifostine benefits CAYA cancer survivors. A recently published RCT (ACCL0431) of a second otoprotective agent in the same class, sodium thiosulfate, showed significant evidence for protection from cisplatin-induced hearing loss in childhood cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,10,48,57 A systematic review by van As et al described two randomized controlled trials (RCTs) and one controlled clinical trial evaluating amifostine as a possible otoprotective intervention in childhood cancer patients. 50 Due to methodological limitations of these clinical trials, there currently is no evidence that otoprotection with amifostine benefits CAYA cancer survivors. A recently published RCT (ACCL0431) of a second otoprotective agent in the same class, sodium thiosulfate, showed significant evidence for protection from cisplatin-induced hearing loss in childhood cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Low quality evidence from one randomized controlled trial and one cohort study showed inconsistent otoprotective benefit in cisplatin-treated survivors cotreated with amifostine. [48][49][50] There is a moderate level of evidence from more recent randomized clinical trials that a second agent in this class, sodium thiosulfate (STS), significantly reduces the severity of hearing loss in CAYA cancer survivors [50][51][52] ; nevertheless, a significant proportion of survivors continue to experience hearing loss; thus, there is insufficient evidence to support less frequent screening of survivors treated with amifostine or STS.…”
Section: Evidencementioning
confidence: 99%
“…Among the many collateral effects resulting from chemotherapy, ototoxicity is one that may cause lesions to the inner ear structures, resulting in hearing loss, normally, sensorineural, bilateral and symmetric, affecting first the higher frequencies 4,5 . Producing free radicals with the use of antineoplastic therapeutic agents may change the cell wall and the cells' genetic material, including the cochlea's hair cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that older age could be a risk factor and that the occurrence of hearing loss can be rapid and can occur at therapeutic doses in the case of cisplatin and amikacin. There are preventive treatments and they should be considered for all patients over the age of 50 who need to be treated with these drugs.…”
Section: Discussionmentioning
confidence: 99%